A three-membered diazo-aluminum heterocycle to access an Al=C π bonding species - Yan, Chenting (2022)
[1+2] cycloaddition between a cyclic (alkyl)(amino)aluminyl anion (3) and diaryldiazomethane affords an AlN2 three-membered ring species (4). Compound (4) is thermally unstable and spontaneously releases N2 gas under the mild reaction condition to generate an ion-separated species 5. An X-ray study shows that the anionic part of 5 bears a considerable short exocyclic Al-C bond, and computational studies involving molecular orbital and natural bond orbital analysis indicate the Al=C π bonding character. The Al=C moiety of 5 undergoes intramolecular C-H activation. Moreover, reaction of 5 with a diazo compound leads to the reduction and complete cleavage of the N=N double bond.